“Difficult” dental patients: a grounded theory study of dental staff’s experiences - Adam Alvenfors; Mersiha Velic; Bertil Marklund; Sven Kylén; Peter Lingström; Jenny Bernson (BDJ Open, 2022)
Abstract Introduction The “difficult” patient is a well-known and potentially negative character in various care contexts. Objectives This study aimed to generate a conceptual framework explaining the main concerns about “difficult” dental patients, and obtain a deeper understanding of their characteristics, how they affect the dental staff and how the staff think and act in order to manage these patients. Methods Ten interviews were conducted with professional dental caregivers, including dentists, dental hygienists, and dental nurses. The audio-recorded interviews were transcribed and analyzed in accordance with the principles of grounded theory. Results The main concern regarding “difficult” dental patients generated a framework of seven descriptive interrelated lower-level categories grounded in the data, subsumed in the core category “balancing subjective difficulties”. The informants perceived the possession of “showing interaction difficulties” and “having bio-psycho-social complexity”, as characteristic features of “difficult” patients, who could further adversely affect the dental staff by “evoking negative emotions and behaviors”, “hampering self-esteem and job satisfaction”, and “impairing life and health in general”. To manage the dental care of these patients, the staff used strategies aimed at “activating internal and external resources” and “creating adaptive treatment relations” with patients. Conclusions The dental staff’s meaning of the phenomenon of “difficult” dental patients points to specific characteristics, effects, and handling strategies. The core category captures the contradictory dynamics of characteristics and affects as these concepts seem interrelated to the caregivers’ handling capacity. The dental staff’s possibility of handling the main concern through balancing subjective difficulties depends on contextual conditions regarding time, to bring the patient and/or oneself at the center of attention. This indicates a need for further research regarding dental interactions and studies generalizing the outlook on “difficult” dental patients.